2016
DOI: 10.1038/srep21022
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of species-specific primers for the molecular identification of ten stored-product psocids based on ITS2 rDNA

Abstract: Psocids are important stored product pests found worldwide that can be spread through grain trade. Most stored-product psocids, including eggs, nymphs, and adults, are very small (~1 mm) and difficult to identify morphologically. Here, we collected 10 economically important stored-product Liposcelis spp. psocids (L. bostrychophila, L. entomophila, L. decolor, L. paeta, L. brunnea, L. corrodens, L. mendax, L. rufa, L. pearmani, and L. tricolor) from 35 geographical locations in 5 countries (China, Czech Republi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…According to previous studies, the intraspecific divergences are rarely greater than 2% and most are less than 1% [ 66 ],. This was also verified in studies of several insect groups, such as Lepidoptera [ 67 ], Piophilidae [ 68 ], Blattidae [ 69 ], Liposcelididae [ 70 ], etc. The recent study of leafhoppers based on COX1 gene fragments also showed that the intraspecific divergence was less than 1% [ 71 ].…”
Section: Resultsmentioning
confidence: 58%
“…According to previous studies, the intraspecific divergences are rarely greater than 2% and most are less than 1% [ 66 ],. This was also verified in studies of several insect groups, such as Lepidoptera [ 67 ], Piophilidae [ 68 ], Blattidae [ 69 ], Liposcelididae [ 70 ], etc. The recent study of leafhoppers based on COX1 gene fragments also showed that the intraspecific divergence was less than 1% [ 71 ].…”
Section: Resultsmentioning
confidence: 58%
“…However, the application of species-specific primers based on ITS sequences in insect identification remains rare. A few studies of mosquitos, thrips, and stored-product psocids have been proposed using ITS species-specific primers 35,36,41,[43][44][45][46] . The results of the present study suggest that the ITS1 sequence variations of Spodoptera with high interspecific variations of > 16% and low intraspecific divergence of < 1.2% (Table 1) can be favourable markers with which to develop species-specific primers for FAW identification.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction process is the same as that described by Zhao et al . in 2016 8 . The DNA was stored at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In order to overcome the limitations of morphological identification methods, many molecular technologies, including restriction fragment length polymorphism (PCR-RFLP) 3 , DNA barcoding 4 , species-specific primer PCR (SS-PCR) 7 , 8 , multiplex endpoint PCR and multiplex TaqMan qPCR 9 , have been developed for psocid identification. Molecular markers are the foundation for molecular identification, and both mtDNA (mitochondrial DNA) and rDNA (ribosomal DNA) are species-specific and can be used as molecular markers for species identification 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%